Coupled Solid and Inverse Antenna Stacks Above Metal Ground as Metamaterial Perfect Electromagnetic Wave Absorbers with Extreme Subwavelength Thicknesses. Issue 10 (26th March 2022) - Kim, Minji; Jung, Kyungmin; Choi, Youmee; Hwang, Seung Sang; Hyun, Jerome K.
Abstract: The ability to completely absorb an electromagnetic (EM) wave with a material much thinner than the wavelength is a prerequisite for achieving ultracompact, flexible, and lightweight EM devices. Herein, a metamaterial microwave perfect absorber is demonstrated as thin as 1/1250 of the target wavelength by coupling an array of metal patches to inverse cross metal antennas through a dielectric separator and with a reflector placed underneath. Compared to a conventional three‐layer absorber, the modified design reduces the resonance frequency by up to tenfolds without altering the patch and dielectric layers, but by reconfiguring the induced current pathways that reorient the dipolar magnetic fields and dramatically boost the magnetic flux. With the reflector, the stack is framed for perfect absorption at the critical coupling condition, which is identified by monitoring the reflection phase shift across the resonance frequency. The study provides guidelines for shrinking the thickness further and can be extended to other frequencies. Abstract : A perfect microwave metamaterial absorber as thin as 1/1250 of the target wavelength is designed by coupling an array of patch antennas to an array of apertures to dramatically enhance the inductance, and by placing a reflector underneath to achieve zero reflection via wave interference. These results provide pathways for achieving unprecedentedly thin electromagnetic wave absorbers.